Evaluating the pyrimidine metabolism in the plant pathogen Phytophthora infestans as a target to control the late blight disease (2016)
This project studied pyrimidine metabolism in Phytophthora infestans, not only because it has been positioned as a model organism to study oomycetes, it can be grown m vitro and in vivo in potatoes and tomatoes (and some Other hosts), it has a sequenced genome and there are available methods for its genetic transformation that allow silencing genes or to work with reporters proteins, but also, due to its historical importance in human migrations, its aggressiveness in the field, the great economic importance of crops affected (potato and tomato) and its increasingly frequent resistance to agrochemicals. The results of the Ph.D. project are presented and discussed in three separate chapters